Desarrollo de una propuesta de un sistema para el tratamiento de aguas residuales provenientes del tratamiento térmico realizado por una empresa Metalmecánica (2017)
The project focused on developing a proposal for a system for residential water treatment the heat treatment process was performed for a metalworking company in order to obtain water that meets the permissible parameters found in Resolution 631 of 2015. For the diagnosis of the current state of the company, a description of the current process was carried out; Taking into account the parameters proposed in the Resolution and the main pollutants of raw water, it sought to identify possible contaminants from the reagents used in steel parts and the composition of the raw material used in the treatment process Thermal, in order to make a comparison and finally get the real contaminants. Once the identification was made, by means of a characterization developed in Analquim S. A. The concentration of the contaminants that are inside the water that is poured to the sewage system was corroborated. Once they obtained the critical parameters, ie they did not meet the specified standards for the dumping of industrial wastewater, proceeded to determine the experimentation required to select the set of treatment that removes the largest amount of impurities. During the experiment, oxido (sodium hypochlorite), coagulant (ferric chloride), flocculant (cationic) and treatment system (grease trap, settler, filters) were selected to be used in order for the water discharged Do not break any parameters.